A20 Haploinsufficiency in a Chinese Patient With Intestinal Behcet's Disease-Like Symptoms: A Case Report - Chen, Yu; Huang, Huanjun; He, Yao; Chen, Minhu; Seidler, Ursula; Tian, De'an; Xiao, Fang (Frontiers in Immunology, 2020)
Objective: Intestinal Behcet’s disease (iBD) is an autoimmune disorder diagnosed by typical intestinal ulcer and systemic Behcet’s disease (BD) manifestations. Haploinsufficiency of A20 (HA20) is a recently described autoinflammatory disease with a phenotype resembling BD which is caused by heterozygous loss-of-function mutations in TNFAIP3 (encoding A20). Methods: We described a 29-year-old female with iBD-like symptoms including relapsing ulceration of intestinal anastomosis, recurrent oral ulcers and vasculitis in extremities. Due to the atypical intestinal ulcer with long segmental involvement and intestinal obstruction, whole exome sequencing (WES) was performed to screen the underlying genetic defect and the identified gene was confirmed by Sanger sequencing. The expression of A20 was evaluated by Western blot. Sanger sequencing and Western blot were also performed in the patient’s family members. Results: A heterozygous mutation of TNFAIP3 (c.305A>G, p. Asn 102 Ser) was identified in the patient. The identical mutation of TNFAIP3 was also found in her father and brother who suffered from recurrent oral ulcers since childhood. Functional experiments revealed that the expression of A20 was decreased in the peripheral blood mononuclear cells from the patient and her family members who carried the TNFAIP3 mutation. Conclusion: We described a Chinese patient developing iBD-like symptoms with a novel heterozygous mutation in TNFAIP3. It proposed that the TNFAIP3 heterozygous mutation (c.305A>G, p. Asn 102 Ser) with an insufficient expression of A20 may be associated with iBD phenotype in patients.